Barista Art: Coffee Education Strategy to The Community - Arifah Fathia Amani; Hanifah Ihsaniyati (Mudra Jurnal Seni Budaya, 2020)
The phenomenon of coffee consumption is currently rife among young people as a lifestyle. Coffee had become one of the ï¬rst global commodities. It has become common to ï¬nd coffee shops, coffee bars, and kiosks. The phenomenon of coffee consumption is related to the role of a baristaâ€™s art. Baristas can be said as people who are experts in making coffee. However, while barista is widely known to the public only in the coffee shop even though many places for baristas can introduce coffee, such as in hotels, restaurants, offices or other public places. This paper aims to describe the role of barista art in educating the public about coffee. This paper is a compilation of several journal articles and books related to coffee, coffee culture, baristas, and the art of making coffee. Article references are obtained through Mendeley by selecting references that correspond to each topic of discussion. Discussion topics include Coffee Culture and Coffee Shop, Baristaâ€™s Action Art, and Coffee Education through Barista Art. The results showed that the existence of baristas had a very important role in educating coffee to the people of Indonesia, especially introducing archipelago coffee. Barista as the main agent in the dissemination of information about coffee so that it is very necessary to have a characteristic of art that must be possessed by the barista as one of the added values â€‹â€‹in the dissemination of information about coffee.